The effects of loan portfolio concentration on Brazilian banks’ return and risk - Tabak, Benjamin M.; Fazio, Dimas M.; Cajueiro, Daniel O. (Journal of Banking & Finance, 2011)
This paper tests whether diversification of the credit portfolio at the bank level leads to better performance and lower risk. We employ a new high frequency (monthly) panel data for the Brazilian banking system with information at the bank level for loans by economic sector. We find that loan portfolio concentration increases returns and also reduces default risk; the impact of concentration on bank’s return is decreasing on bank’s risk; there are significant size effects; foreign and state-owned banks seem to be less affected by the degree of diversification. An important additional finding is that there is an increasing concentration trend after the breakout of the recent international financial crisis, specially after the failure of Lehman Brothers.